Rediscovering the Tradition of Painted Caribou Belongings in Eeyou Istchee: A Community-Based and Community-Led Research Project - Orr, Margaret; Mukash, Natasia; Menarick, Paula (KULA, 2021)
One of the core programming goals at Aanischaaukamikw Cree Cultural Institute is to rediscover, relearn, and reintroduce the traditions of our historic belongings through the display, study, and research of belongings currently cared for by museums outside our region. In 2017, we received funding from the Canada Council of the Arts for a multi-year research and knowledge creation project, "Rediscovering the Tradition of Painted Caribou Coats in Eeyou Istchee." Our project brought Eeyou knowledge together with surviving examples of painted caribou coats and accessories from the eighteenth and nineteenth centuries usually referred to, and classified as, "Naskapi" by museums and "experts" outside our region.